Zootherapeutics utilized by residents of the community Poço Dantas, Crato-CE, Brazil - Almeida Waltécio O; Ribeiro Samuel C; Brito Samuel V; Ferreira Felipe S; Alves Rômulo RN (BMC, 2009)
Abstract Background Animals have been used as a source of medicine in Brazil since ancient times, and have played a significant role in healing practices. Specifically in Northeast Brazil, zootherapy is a very common practice, and together with medicinal plants, it plays an important role as a therapeutic alternative. In the state of Ceara, no works have been carried out on rural communities with regard to use of zootherapeutics, even though the practice of zootherapy is common in this region. Therefore, the aim of this study was to analyze the use of medicinal animals in a rural community (Poco Dantas) in the municipality of Crato, Ceara, Brazil. Methods The field survey was carried out from October 2008 to January 2009 by conducting interviews using structured questionnaires with 72 people (33 men and 39 women), who provided information on animal species used as remedies, body parts used to prepare the remedies, and ailments for which the remedies were prescribed. We calculated the informant consensus factor (ICF) to determine the consensus over which species are effective for particular ailments, as well as the species use value (UV) to determine the extent of utilization of each species. Results A total of 29 species, distributed in 17 families were categorized as having some medicinal property. The taxa most represented were: mammals (9), insects (7), reptiles and birds (4). Progne chalybea, a species not previously recorded as being of medicinal use, was cited in the present work, where it is utilized in the treatment of alcoholism. The animals are used in the treatment of 34 diseases or symptoms, where sore throat, inflammations and cough are the ailments with the greatest number of citations. Conclusion The data show that zootherapy represents an important therapeutic alternative for the inhabitants of the community. New studies on medicinal fauna should be conducted with the aim of determining the exploitation level of the species utilized, promoting sustainable development of medicinal species that are eventually threatened, and preserving and disseminating the knowledge developed by traditional individuals of the community.